Attitudes and Perceptions of Online Instructors towards the Use of Social Media in Teaching and Learning in East African Countries - Kimani , Jam (International Journal of Online and Distance Learning, 2023)
Purpose: The aim of this study is to explore the attitudes and perceptions of online instructors towards the use of social media in teaching and learning in East African countries Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the attitudes and perceptions of online instructors towards the use of social media in teaching and learning in East African countries. Preliminary empirical review revealed that online instructors in East African countries perceive social media to be a useful tool in teaching and learning, as it enhances student engagement and facilitates the exchange of information and resources. Concerns about privacy, information security, and access to social media platforms were identified in some universities in the region. Positive attitudes towards the use of social media in teaching and learning were found in most of the studies reviewed. Unique Contribution to Theory, Practice and Policy: The Technology Acceptance Model (TAM), Social Presence Theory and Community of Inquiry (CoI) Framework may be used to anchor future studies on the attitudes and perceptions of online instructors towards the use of social media in teaching and learning in East African countries. Universities in East African countries should develop policies and guidelines on the use of social media in teaching and learning. Online instructors should be provided with training and support on how to use social media effectively in teaching and learning. Universities in the region should invest in social media technologies to enhance the teaching and learning experience for students.